Contraceptives: a guide to product selection - Petrus S. Steyn; J. Kluge (South African Family Practice)
Contraception remains one of the most cost-effective public health measures to reduce rates of maternal and infant mortality. General practitioners (GPs) who provide contraceptive counselling should be able to discuss every eligible contraceptive method for the specific woman. In addition to contraceptive counselling, the GP can address other sexual and reproductive health issues, including the prevention of sexually transmitted infections at the same visit, providing a holistic approach. The World Health Organization (WHO) has online tools available to aid in contraceptive choice. The WHO Medical Eligibility Criteria for Contraceptive Use (WHO MEC) provides evidence-based recommendations to ensure that patients are medically fit to use a particular method and can safely select the most appropriate method of contraception. The Faculty of Sexual and Reproductive Healthcare (FSRH) of the Royal College of Obstetricians and Gynaecologists and the National Institute for Health and Clinical Effectiveness (NICE) also provide extensive guidelines on the use of various contraceptives. This article guides product choice available in South Africa.